2009
DOI: 10.1107/s1600536809021114
|View full text |Cite
|
Sign up to set email alerts
|

4′-(4-Methoxyphenyl)-1,1′,1′′-trimethyldispiro[indoline-3,2′-pyrrolidine-3′,3′′-pyrrolidine]-2,2′′,5′′-trione

Abstract: In the title compound, C24H25N3O4, the pyrrolidine ring adopts an envelope conformation while the pyrrolidine-2′′,5′′-dione ring adopts a twist conformation. The indoline unit is planar [maximum deviation of −0.050 (9) Å] and forms a dihedral angle of 40.36 (4)° with the methoxy­phenyl ring. Intra­molecular C—H⋯O hydrogen bonds are observed. In the crystal, mol­ecules are linked into a two-dimensional network parallel to the ab plane by inter­molecular C—H⋯O hydrogen bonds and C—H⋯π inter­actions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2015
2015
2016
2016

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 11 publications
0
5
0
Order By: Relevance
“…They also inhibit retroviral reverse transcriptases [i.e., human immunodeficiency virus type 1 (HIV-1)], cellular DNA polymerases, protein kinases (Bellina & Rossi, 2006). They also act as antidepressant agents (Wró bel et al, 2013), antibiotics (Nirmala et al, 2009), anticonvulsant, sphingosine-1-phosphate (S1P) receptor agonists, malic enzyme inhibitors, ketoamide-based cathepsin K inhibitors and human melanocortin-4 receptor agonists (Babu et al, 2012). Quinoline derivatives have been synthesized and explored for their analgesic activity, anti-allergetic properties and in treating Alzheimer's disease (AD).…”
Section: Structure Descriptionmentioning
confidence: 99%
“…They also inhibit retroviral reverse transcriptases [i.e., human immunodeficiency virus type 1 (HIV-1)], cellular DNA polymerases, protein kinases (Bellina & Rossi, 2006). They also act as antidepressant agents (Wró bel et al, 2013), antibiotics (Nirmala et al, 2009), anticonvulsant, sphingosine-1-phosphate (S1P) receptor agonists, malic enzyme inhibitors, ketoamide-based cathepsin K inhibitors and human melanocortin-4 receptor agonists (Babu et al, 2012). Quinoline derivatives have been synthesized and explored for their analgesic activity, anti-allergetic properties and in treating Alzheimer's disease (AD).…”
Section: Structure Descriptionmentioning
confidence: 99%
“…For the biological activity of pyrrolidine and indole derivatives, see: Babu et al (2012); Savithri et al (2014); Govind et al (2003); Gayathri et al (2005); Li et al 2004; Bellina & Rossi (2006). For the crystal structure of a similar dispiroindoline compound, see: Nirmala et al (2009) Hydrogen-bond geometry (Å , ).…”
Section: Related Literaturementioning
confidence: 99%
“…Optically active pyrrolidines have been used as intermediates, chiral ligands or auxiliaries in controlled asymmetric synthesis (Savithri et al, 2014). Pyrrolidine compounds are reported to exhibit antimicrobial, antifungal (Govind et al, 2003), anti-influenza virus (Gayathri et al, 2005), anti-inflammatory, antitumor (Li et al, 2004), inhibit retroviral reverse transcriptases [i.e., human immunodeficiency virus type 1 (HIV-1)], cellular DNA polymerases, protein kinases (Bellina and Rossi, 2006), antibiotics (Nirmala et al, 2009), anticonvulsant, sphingosine-1-phosphate (S1P) receptor agonists, malic enzyme inhibitors, ketoamide-based cathepsin K inhibitors, human melanocortin-4 receptor agonists (Babu et al, 2012). Indole compounds can be used as bioactive drugs.…”
Section: Related Literaturementioning
confidence: 99%
“…For biological activities of pyrrolidine derivatives, see: Aravindan et al (2004); Gayathri et al (2005); Seki et al (2013); Li & Xu (2004); Arun et al (2014); Govind et al (2003); Nirmala et al (2009); Sharma & Soman (2015); Bellina & Rossi (2006); Babu et al (2012). For related structures, see: Savithri et al (2014 Hydrogen-bond geometry (Å , ).…”
Section: Related Literaturementioning
confidence: 99%
“…Optically active pyrrolidines have been used as intermediates, chiral ligands or auxiliaries in controlled asymmetric synthesis (Savithri et al, 2014). Synthetic spiro pyrrolidine derivatives exhibit activity against the aldose reductase enzyme, which controls influenza virus (Gayathri et al, 2005) and also pyrrolidine compounds are reported to exhibit ischemic stroke (Seki et al, 2013), anti-inflammatory (Li & Xu, 2004), antitumor (Arun et al, 2014), antimicrobial, antifungal (Govind et al, 2003), antibiotic (Nirmala et al, 2009) and anti-diabetic (Sharma & Soman, 2015) activities and inhibition of retroviral reverse transcriptases [i.e., human immunodeficiency virus type 1 (HIV-1)], cellular DNA polymerases and protein kinases (Bellina & Rossi, 2006). They are also anticonvulsants, sphingosine-1-phosphate (S1P) receptor agonists, malic enzyme inhibitors, ketoamide-based cathepsin K inhibitors and human melanocortin-4 receptor agonists (Babu et al, 2012).…”
Section: Related Literaturementioning
confidence: 99%